PENGARUH KEPUTUSAN INVESTASI, KEBIJAKAN DEVIDEN, KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Jannes Sinaga; Halomoan Sihombing; Danri Toni Siboro (Komunitas Manajemen Kompetitif, 2026)
This study aims to determine the effect of investment decision (PER), dividend policy (DPR), and debt policy (DER), partially and simultaneously on firm value in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange during the 2022–2024 period. The period used in this study was three years, from 2022 to 2024. The sample was taken using a purposive sampling method. The population in this study consisted of all manufacturing companies in the food and beverage sub-sector that were listed and still listed on the Indonesia Stock Exchange during the 2022–2024 period. Based on predetermined criteria, several companies were obtained as research samples with an observation period of three years (2022–2024). The data were analyzed using multiple linear regression. Based on the results of data analysis, it can be concluded that investment decision (PER) has a positive and significant effect on firm value with a t-value of 5.393 and a significance value of 0.000, therefore the first hypothesis is accepted. Dividend policy (DPR) has a negative and significant effect on firm value with a t-value of -2.145 and a significance value of 0.036, therefore the second hypothesis is accepted. Debt policy (DER) has a negative and significant effect on firm value with a t-value of -2.452 and a significance value of 0.017, therefore the third hypothesis is accepted. The goodness of fit test shows that investment decision (PER), dividend policy (DPR), and debt policy (DER) simultaneously affect firm value. This is indicated by the F-value of 12.492 and a significance value of 0.000. The coefficient of determination (R²) of 0.388 indicates that the influence of investment decision (PER), dividend policy (DPR), and debt policy (DER) on firm value is 38.8%, while the remaining 61.2% is explained by other variables not examined in this study